Literature Review: Problems of Mathematics Learning in Schools - Bhaskoro Prasetyo Adi Maryanto; lelly Nur Rachmawati; Ilham Muhammad; Rahmad Sugianto (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
Problems that occur in mathematics learning are essential to pay attention to. Problems in mathematics learning are problems that must be resolved with the right solution. This research aims to conduct a literature review on mathematics learning problems in schools. The method used in the study is a literature review. The sample used is the research results related to mathematics learning problems at the elementary, junior high, high, and college levels from student and teacher factors. Data was collected by collecting all published articles from the latest year according to educational level. Then, analysis and conclusions are drawn based on the data obtained. The research results show that the problems found at each station are different. So, the solution used must be the problems faced.